If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(ax + b + -1c) + 2 = 0 (ax * 3 + b * 3 + -1c * 3) + 2 = 0 (3ax + 3b + -3c) + 2 = 0 Reorder the terms: 2 + 3ax + 3b + -3c = 0 Solving 2 + 3ax + 3b + -3c = 0 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + 3ax + 3b + -2 + -3c = 0 + -2 Reorder the terms: 2 + -2 + 3ax + 3b + -3c = 0 + -2 Combine like terms: 2 + -2 = 0 0 + 3ax + 3b + -3c = 0 + -2 3ax + 3b + -3c = 0 + -2 Combine like terms: 0 + -2 = -2 3ax + 3b + -3c = -2 Add '-3b' to each side of the equation. 3ax + 3b + -3b + -3c = -2 + -3b Combine like terms: 3b + -3b = 0 3ax + 0 + -3c = -2 + -3b 3ax + -3c = -2 + -3b Add '3c' to each side of the equation. 3ax + -3c + 3c = -2 + -3b + 3c Combine like terms: -3c + 3c = 0 3ax + 0 = -2 + -3b + 3c 3ax = -2 + -3b + 3c Divide each side by '3x'. a = -0.6666666667x-1 + -1bx-1 + cx-1 Simplifying a = -0.6666666667x-1 + -1bx-1 + cx-1 Reorder the terms: a = -1bx-1 + cx-1 + -0.6666666667x-1
| 27y^2-12x^2=0 | | 50w^2-32w^4=0 | | 3c+8=32 | | =90 | | x+3n=40 | | 5p^2=-20+29p | | -(5-4x)=19 | | x+1/9=x+3/4 | | 4x^2-5x+16=8x+7 | | x^2-9xy+20y^3=0 | | 0.5(x+10)+1.5x-3=12 | | -6x+7p+16x= | | x^2+10xy-24y^2=0 | | 6t+12s= | | 5/4n=-41/6 | | -2k-2k-5=0 | | 4x+5=6x-11 | | x^2+7xy+6y^2=0 | | 11x=185 | | 4-6x/5=7 | | 6x-1=-q+20 | | -5b^2-4b-5=0 | | 150x=1800 | | 6f+7/7-5f-f | | 10.2s=61.2 | | x^2-15xy+26y^2=0 | | 4(-3/5)(3a+4)=7 | | -8(3+7x)+5=39+2x | | -2v-4=-2v | | 4x+27=x+12 | | 5(2x-2)=3(4-2x) | | -2-5n=-5n^2 |